The Impact of Diversification to Risk and Return of a Finance Company - Juliana Surijanto (Business and Entrepreneurial Review, 2006)
As the economy began to recover, some believed that only financing companies who focused in consumer financing have a better opporttrnity to generate profit compared to those who diversify their product on leasing. Thus, the objectives of this researc where to identify the following: did risk variables have an impact to return? And did product diversification have and impact to the risk and return of financing companies. A non proportional stratified random sampling was used to get samples from the total population listed in APPI (lndonesian Financing Company Association). Multiple regression analysis was adopted and disclosed that only Inefficiency risk variable impacts to Profit Margin on Sales ratio, while the Inliquidity risk impact to both ROA and ROE. All risk variables will simultaneously impact to ROA and ROE significantly, while product diversification is proven not having any influences to the relation of risk and return of a financing company. The result also concluded that consumer financing was enjoying rapid grow cornpared to leasing, and managed to recover faster from economic crisis due to aggressive support of automotive industry and because of the traumatic experience of some financing companies in dealing with leasing business, finally ended in debt restructuring program under IBRA's observation.